KONSELING ISLAMI DAN PROBLEM SOLVING - Ali Musa Lubis (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
Human always face many kinds of problem in their life. Some problems can solve easily, the others are difficult to solve and its causes mental disorders. As a khalifatullah in al-ardl, human has given potency to face the problems in their life. In Islamic counseling study, problem solving is the part of study that may help to answer the problem faced by human. The main study of this paper is related to strategies steps of problem solving in Islamic counseling perspective.